Sensorless control of PMSM using generalized extended state observer and adaptive resistance estimation. Issue 11 (10th August 2020) - Ge, Yang; Yang, Lihui; Ma, Xikui
Abstract : In this study, a novel sensorless control of the surface‐mounted permanent‐magnet synchronous motor (PMSM) is proposed. Firstly, by taking the derivative of the back electromotive force (EMF), the high‐order voltage equations of PMSM, in which the dominant time‐changing parts of back‐EMF are separated and modelled, are deduced. Then a generalised extended state observer, which possesses the preferable tracking ability for time‐varying states, is designed to estimate the back‐EMF. Also, since the difference between the measured stator resistance and its real value, which changes with temperature, will lead to position errors, a resistance estimation scheme is proposed. Compared with the conventional sensorless method of PMSM, the proposed method can provide a more accurate and smooth position and speed estimation under resistance uncertainty without extra filter and compensator. Furthermore, since the effects of speed and current change rate are taken into consideration, the application of the proposed scheme is broadened. The effectiveness of the proposed method is verified by the experiments in different cases.